SLEEP AND DREAMING IN THE KOMI-PERMYAKS’ TRADITIONAL CULTURE - Goleva, T.G. (Perm Federal Research Centre Journal, 2016)
Traditions of sleep have inevitably evolved in the culture of any nation. Modern ethnographic field data reveal the elements of the anthropology of sleep in the Komi-Permyaks’ traditional culture. The author describes the material culture, the rituals associated with sleep, beliefs and ideas about sleep and dreaming. The study allows defining the semantics of some customs and the Komi- Permyaks’ rational knowledge about the nature of sleep.